Anne Chotzinoff Grossman & Lisa Grossman Thomas: Lobscouse and Spotted Dog - Jaine, Tom (Petits Propos Culinaires, 2024)
Anne Chotzinoff Grossman & Lisa Grossman Thomas: Lobscouse and Spotted Dog: W. W. Norton and Company, New York and London, 2000: ISBN 0-393-32094-4: 304 pp., b/w illus., p/b, $16.95.